Agricultural policies and technical efficiency of wheat production in Kazakhstan and Russia: Evidence from a stochastic frontier approach - Alisher Tleubayev; Ihtiyor Bobojonov; Linde Götz (Journal of Agricultural and Applied Economics, 2022)
We utilize a unique primary data set of farms in Russia and Kazakhstan to investigate the link between policy reforms and technical efficiency. These countries have heavily subsidized their domestic agricultural production over the last decade, with a total of around USD 76 billion USD and USD 11.5 billion USD in government funding directed towards the agricultural sectors in Russia and Kazakhstan, respectively. Results of a stochastic frontier analysis make evident that variable inputs, such as fertilizer, have a relatively large influence on wheat production compared to land. Nearly every fifth farm has a technical efficiency level lower than 60%, suggesting significant unrealized production potential. While our analysis shows a negative relation between subsidies and efficiency, other factors, such as farmer's education, cooperative and agroholding membership, and participation in insurance programs, are positively related to farm efficiency. The results imply that the governments and policymakers could mobilize the unutilized wheat production potential by improving the farmer education system, fostering cooperation among farms, and developing functioning farm insurance schemes.
Keywords: Q12; Q14; Q18; 330; food security; KRU countries; stochastic frontier analysis; subsidies; technical efficiency